Delivering tourism intelligence : from analysis to action - Pearce, Philip L.; Oktadiana, Hera (Bridging tourism theory and practice, 2020)
This volume demonstrates that tourism research can deliver quality implications for a range of stakeholders. Contributions from authors across the continents serve to illustrate ways in which academic analysis can, and does, result in action.